Kewenangan Ptun Mengadili Kasus Perizinan (Studi Kasus Putusan Nomor 4/P/FP/2020/PTUN.PL) - Rayhan, Ahmad; Taqiyya, Shafiah; Safitriana, Rika; Sfitriana, Rika (Fakultas Hukum Universitas Primagraha, 2023)
The Welfare State and Public Services are closely connected in the implementation of an independent economic system. The Welfare State ensures basic needs are met through government management of tax revenue. In Indonesia, Public Services are regulated by Law Number 30 of 2014. The case study of fictitious positive involves PT Griya Martua Tomorindah, the Regent of Morowali, and the Governor of Central Sulawesi. The court ruled in favor of the respondent, rejecting the petitioner's request. The resolution of fictitious positive disputes is governed by Supreme Court Regulation Number 8 of 2017. The objects of dispute included missing mining permit documents and lack of response to work plan and budget approval. The Court rejected the request due to a missed application deadline. The Administrative Court (PTUN) has jurisdiction over fictitious positive disputes in public administration. However, the objects in this case did not meet the criteria as they didn't exceed the time limit. The Court accepted the respondent's error in persona exception regarding the second object. The author agrees with the Court's verdict in this case as it was appropriate.